Pseudocapacitive Anode Materials toward High‐Power Sodium‐Ion Capacitors. Issue 10 (9th April 2021) - Chang, Xiaoqing; Huang, Tingyi; Yu, Jiayu; Li, Junbin; Wang, Jian; Wei, Qiulong
Abstract: Sodium‐ion storage technology holds great promise for large‐scale, sustainable, and low‐cost green energy storage systems. Overcoming the main limitations of sluggish Na + diffusion kinetics and achieving high‐power sodium‐ion storage devices is critical but full of challenges. Recently, emerging pseudocapacitive sodium‐ion storage materials are attracting attention due to their superior rate capability and other comprehensive electrochemical performance. Herein, this review covers the charge storage mechanism, features, and performance of pseudocapacitive sodium‐ion storage anode materials and the assembled sodium‐ion capacitors. The research processes of state‐of‐the‐art pseudocapacitive sodium‐ion storage anode materials, which display remarkable rate performance, high specific capacity and cycling stability, are introduced and discussed. Using the pseudocapacitive anode materials, advanced sodium‐ion capacitors deliver high energy density at high power density. In the end, the outlooks of pseudocapacitive sodium‐ion storage materials toward future high‐power sodium‐ion capacitors are briefly proposed. Abstract : The powers that be : Pseudocapacitive sodium‐ion storage anode materials deliver both high specific capacity and high‐rate capability (finishing a charge or discharge in minutes). In this review, we cover the charge storage mechanism, electrochemical reaction features, and performance of pseudocapacitive sodium‐ion storage anode materials and advanced sodium‐ion capacitors that achieve both high energy and high power densities.